2009
DOI: 10.1002/pola.23622
|View full text |Cite
|
Sign up to set email alerts
|

Strong activation of MgCl2‐supported Ziegler‐Natta catalysts by treatments with BCl3: Evidence and application of the “cluster” model of active sites

Abstract: Heterogeneous Ziegler‐Natta precatalysts (with phthalate as internal donor) were modified by treatments with BCl3 (2 h in heptane; T = 20–90 °C; B/Ti = 0.1–5) before their use in the polymerization of propylene to modify the active sites distribution. If performed on previously “detitanated” precatalysts, the treatment leads to a strong increase of productivity (up to one order of magnitude) without drastic modifications of polypropylenes properties (tacticity, molecular weight distribution). In addition, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…All other precatalysts were found to be active for the polymerization of propylene. As previously reported,13 a drastic increase of productivity was evidenced after treatment with BCl 3 of the “detitanated” precatalyst and the activity of initial precatalyst is surpassed (27,300 kg/molTi/h for T 0 + B 30 ; 2700 kg/molTi/h for T 0 ; and 9700 kg/molTi/h for ref. ; Table 1).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…All other precatalysts were found to be active for the polymerization of propylene. As previously reported,13 a drastic increase of productivity was evidenced after treatment with BCl 3 of the “detitanated” precatalyst and the activity of initial precatalyst is surpassed (27,300 kg/molTi/h for T 0 + B 30 ; 2700 kg/molTi/h for T 0 ; and 9700 kg/molTi/h for ref. ; Table 1).…”
Section: Resultssupporting
confidence: 71%
“…In summary for the first time, the distribution of active sites has been slightly modified by introduction of Lewis acid such as SiCl 4 and SnCl 4 with an increase of the selectivity of propylene insertion (tacticity) what was not observed with BCl 3 . A variable gain of activity is also observed following the order: BCl 3 >> SiCl 4 > SnCl 4 without a significant increase of polypropylenes molecular weight ( M n , M w ), which indicates an increase of the number of active sites as already observed with BCl 3 13. On the other hand, the distribution of active sites regenerated by SiCl 4 and SnCl 4 after controlled “detitanation” by thermal treatment is not identical to the original one (as observed with BCl 3 ): the relative amount of “isotactic” active sites is increased corresponding either to an increase of the number of intrinsically “isotactic” preactive sites and/or to an increase of the number of sites, which are converted by External Lewis Base and AlEt 3 in “isotactic” active sites.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…This finding was in line with other researchers results which were published before. [35][36][37] Furthermore, it was observed that the activity increase in the presence of FeCl 3 -SiCl 4 mixture was higher than it in the presence of FeCl 3 alone. It is possible that besides halogen-donating ability of SiCl 4 which acts as promoter in ethylene polymerization, the synergistic effect of double metal halide and metalloid compounds generated more active sites, which were suitable for ethylene polymerization.…”
Section: Ethylene Polymerization Resultsmentioning
confidence: 86%